An Experimental Investigation of Hole Geometry in Friction Drilling - Ozler, Latif; Dogru, Nulifer (Taylor & Francis Inc, 2013)
In this study, AISI 1010 steel square-tube materials were drilled on a computer numerical control (CNC) machine center by friction drilling. In friction drilling, the tungsten carbide tools with different friction angle and diameters were used. During drilling, the effects of machining parameters on the thrust force and the hole zone temperature were investigated. The washer geometry, the bushing height, and the petal geometry were examined with respect to drilling conditions such as friction cone angle, feed rate, and drilling speed. According to the results of the experiments, the hole zone temperature rose with increasing drilling speeds and decreasing feed rates. Accordingly, high drilling speeds improved washer geometry, and thus the bushing height expanded. It has been found out that the washer and the bushing geometry were distorted due to high feed rates.
Keywords: Drilling; Force; Friction; Geometry; Temperature